Pengendalian Kualitas Produk Dengan Metode Statistical Quality Control (SQC) Untuk Mengurangi Produk Gagal Pada Sri Bakery - Sidah Sidah; Mochammad Nuruddin; Deny Andesta (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2022)
This activity is to determine the quality control of pastel products at the partner in May 2020 - April 2021. Sri Bakery is a home- business engaged in food processing since 1992. The resulting pastel products often suffer from product failures such as uneven shape, charring, and leaking of contents. The object of this activity is the number of production and the number of defective products in pastel products. Data were collected by direct interviews which were then processed and analyzed using the Statistical Quality Control (SQC) method using statistical tools in the form of check sheets, histograms, pareto diagrams, scatter diagrams, p-charts, and fishbone diagrams. The results of data processing show that Sri Bakery is still within reasonable limits, but there needs to be corrective action to reduce failed products. On average pastels fail every month, reaching 5% of the total production produced. Actions that need to be taken to reduce product failure are that partner needs to use statistical methods to identify the category of defects and the factors that cause product failure to occur, besides that partner needs to make a Standard Operational Procedure (SOP) so that the production process avoids errors.